Patience Epps and Lev Michael (eds.). 2023. Amazonian languages; Language isolates I: Aikanã to Kandozi-Chapra (pp. i-lxi, 1-657 + “Index” [24 pp. not numbered]); II: Kanoé to Yurakaré (pp. i-xiii, 659-1352 + “Index” [26 pp. not numbered]); An international handbook (Handbooks of Linguistics and Communication Science // Handbücher zur Sprach- und Kommunikationswissenschaft (HSK) series, vols. 44.1-2 of HSK 44). Berlin–Boston: De Gruyter Mouton - Majewicz, Alfred F. (Lingua Posnaniensis, 2024)
Review